ANALISIS IMPLEMENTASI PROGRAM INOVASI AKSI JITU ATASI MASALAH GIZI DI PUSKESMAS PAGENTAN II KABUPATEN BANJARNEGARA - Rustiawan, Asep; Mustika Hening Khasanah (Jurnal Kesehatan dan Pengelolaan Lingkungan, 2024)
The Effective Action Innovation Program to Overcome Nutritional Problems (AJA MAGIZ) is an innovation program to overcome the problem of stunting in toddlers, implemented starting in 2021 at the Pagentan II Banjarnegara Community Health Center. The aim of this research is to analyze the implementation of the AJA MAGIZ program in the field using the theoretical approach of Doland Van Meter and Carl Van Horn. Qualitative research with a case study design involving 2 main informants and 7 triangulated informants. Data collected: goals, objectives and criteria for program success; implementation, guidebooks, and funds; activity schedule, division of tasks, problem solving in the field; community leaders and household participation. Data were collected using in-depth interview techniques and analyzed using the Manual Data Analysis Procedure. The research results show that program implementers: understand the target criteria, objectives and success of the program well; have adequate knowledge and skills but the number of implementing staff and funds is still lacking; carry out activities according to the schedule that has been prepared, can solve technical problems in the field; Community leaders provide support and the household were participate actively. The results of the analysis concluded that the AJA MAGIZ program was implemented well and succeeded in reducing the number of stunted toddlers by 73%. It is important to meet the shortage of implementing staff and funds.